Crosslinked poly(ethylene oxide) containing siloxanes fabricated through thiol‐ene photochemistry. Issue 13 (16th March 2015) - Kusuma, Victor A.; Roth, Elliot A.; Clafshenkel, William P.; Klara, Steven S.; Zhou, Xu; Venna, Surendar R.; Albenze, Erik; Luebke, David R.; Mauter, Meagan S.; Koepsel, Richard R.; Russell, Alan J.; Hopkinson, David; et al.
ABSTRACT Homogenous amphiphilic crosslinked polymer films comprising of poly(ethylene oxide) and polysiloxane were synthesized utilizing thiol‐ene "click" photochemistry. A systematic variation in polymer composition was Carried out to obtain high quality films with varied amount of siloxane and poly(ethylene oxide). These films showed improved gas separation performance with high gas permeabilities with good CO2/N2 selectivity. Furthermore, the resulting films were also tested for its biocompatibility, as a carrier media which allow human adult mesenchymal stem cells to retain their capacity for osteoblastic differentiation after transplantation. The obtained crosslinked films were characterized using differential scanning calorimetry, dynamic mechanical analysis, thermogravimetric analysis, FTIR, Raman‐IR, and small angle X‐ray scattering. The synthesis ease and commercial availability of the starting materials suggests that these new crosslinked polymer networks could find applications in wide range of applications. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2015, 53, 1548–1557